Pengaruh Penggunaan Lipstik Terhadap Kepercayaan Diri Perempuan - Arissa, Agusti Putri (Universitas Negeri Jakarta, 2025)
This study aims to examine the influence of lipstick use on women's self-confidence, particularly within the context of urban life. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 15 women aged 20–35 who actively use lipstick in their daily activities. The results reveal that lipstick functions not merely as a cosmetic tool but also as a symbol of personal strength, a social instrument, and a psychological necessity. Participants expressed that lipstick use enhances their confidence in both social and professional situations. However, some also recognized a symbolic dependency conditioned by social aesthetic standards. These findings support the view that beauty products play a complex role in shaping women’s identity and psychological state. Therefore, it is essential to promote more inclusive and empowering beauty campaigns.